Platelet factor 4/heparin antibody (IgG/M/A) in healthy subjects: a literature analysis of commercial immunoassay results - Arepally, Gowthami M. (2008)
PURPOSE: We determined the seroprevalence of platelet factor 4 (PF4)/heparin antibodies in healthy subjects. METHODS: A literature search identified studies in which healthy subjects were evaluated using commercial immunoassays for PF4/heparin antibody (IgG/M/A). Proportions of test-positive subjects were calculated, by assay. RESULTS: Across 11 eligible studies, 860 healthy subjects were tested using the Stago enzyme-linked immunosorbent assay (ELISA) (nine studies), GTI ELISA (three studies), and/or DiaMed particle gel immunoassay (PGIA) (three studies). Seropositivity occurred in 17 of 790 (2.2%, 95% CI, 1.1–3.2%) subjects by Stago ELISA, one of 100 (1.0%, 95% CI, 0–3.0%) subjects by GTI ELISA, and three of 70 (4.3%, 95% CI, 0–9.0%) subjects by PGIA (P > 0.20). Of seven seropositive subjects tested further, none had platelet-activating antibodies. CONCLUSION: Commercial immunoassays detect PF4/heparin antibody in 1.0–4.3% of healthy subjects. Because this “background” prevalence overlaps seropositivity rates in heparin-treated patients in various clinical settings, normality cut-offs may require refinement.